Exploring Strategies to Promote Waste Management in Education for A Sustainable Future: A Systematic Literature Review - Amanda, Arnie; Solihat, Rinin; Riandi, Riandi; Habibaturrohmah, Zuana (BRILIANT: Jurnal Riset dan Konseptual, 2025)
As the global community faces escalating environmental challenges, integrating waste management into educational curricula is essential for fostering sustainable practices among future generations. By equipping students with the knowledge and skills to understand the impact of waste, we empower them to take active roles in promoting environmental stewardship and advocating for responsible consumption. This article presents a systematic literature review exploring effective strategies for promoting waste management in educational settings, framed within the context of Education for Sustainable Development (ESD). The PRISMA 2020 systematic literature review method was used, with Scopus as the primary database. Out of 761 collected articles, 20 met the criteria for thematic-qualitative analysis. By synthesizing findings from a range of studies, this article identifies key themes and successful models that enhance student awareness and action regarding waste management. The insights gained contribute to a deeper understanding of how ESD can effectively shape waste management practices, ultimately supporting the development of a sustainable future. This work highlights the critical role of education in cultivating environmentally responsible behaviors and encourages educators to adopt innovative strategies that align with ESD principles.